FIKIH DALAM WATAK FORMALISTIK DAN SUFISTIK - MUBARAK MUBARAK (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2014)
If Islamic jurisprudence (fiqh) were understood as a product of Law based on legal-formal aspect, it would give efforts to manipulate the law (hilah hukmiyyah), then Islamic jurisprudence (fiqh) will lose its power. We know that Islamic Jurisprudence (fiqh) conceptualized by scholars (ulama in fiqh) should not leave its philosophy meaning. The aims of this writing are to combine two perspective, Islamic jurisprudence and tasawuf. Based on library research and used qualitative approach, it founded that combining between formalistic and sophistic become Islamic jurisprudence as a solution to solve many social problems.